Kesejahteraan Psikologis dan Kualitas Hidup Penderita Diabetes Mellitus Type 2 - Sasmiyanto Sasmiyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to prove the correlation between psychological well-being and quality of life of people with type 2 diabetes mellitus in Bondowoso. This type of research is a correlational study with a cross sectional approach. The results of the study based on statistical tests found the average value of the psychological well-being of clients 120.5778 which can be said to be quite good. The quality of life of respondents has an average score of 53,389 which can be said to be quite good. The results of statistical analysis show that the p value is 0.004. Conclusion, there is a significant relationship between psychological well-being and quality of life of people with diabetes mellitus. The effect of psychological effects on the condition of the body is huge. Keywords: Diabetes Mellitus type 2, Psychological Well-being, Quality of Life